2017
DOI: 10.1080/00016489.2016.1269945
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain control after tonsillectomy: dexametasone vs tramadol

Abstract: When the control and the dexamethasone groups were compared; there were statistically significant differences in pain scores at post-operative 15 and 30 min, whereas there was no statistically significant difference in pain scores at other hours. When the control and tramadol groups were compared, there was a statistically significant difference in pain scores at all intervals. When tramadol and dexamethasone groups were compared, there was no statistically significant difference in pain scores at post-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Seven of them were considered inappropriate for inclusion in the final analysis due to methodological constraints or non‐English full‐text publication. The selected articles consisted of 12 RCTs enrolling a total of 972 children, among which 345 were assigned to the tramadol peritonsillar infiltration group and the remaining 627 in the placebo or active comparator groups. All of these studies met the criteria to be included in the final qualitative appraisal, whilst 8 RCTs incorporating both a comparison to the placebo group and tramadol dosing of 2 mg/kg were deemed eligible to be included in the quantitative analysis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven of them were considered inappropriate for inclusion in the final analysis due to methodological constraints or non‐English full‐text publication. The selected articles consisted of 12 RCTs enrolling a total of 972 children, among which 345 were assigned to the tramadol peritonsillar infiltration group and the remaining 627 in the placebo or active comparator groups. All of these studies met the criteria to be included in the final qualitative appraisal, whilst 8 RCTs incorporating both a comparison to the placebo group and tramadol dosing of 2 mg/kg were deemed eligible to be included in the quantitative analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the included RCTs implemented a 3‐arm study design, whilst 2 or 4 comparison groups were incorporated in 4 and 3 RCTs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies [8,16,18] reported that dexamethasone was administered by local infiltration. The result showed that dexamethasone was favoured for preventing PONV (RR 0.58, 95% CI 0.341-0.99, I 2 =0%; Figure 4).…”
Section: Dexamethasone Local Infiltrationmentioning
confidence: 99%